2003
DOI: 10.1016/s1095-6433(03)00167-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition during growth and starvation of early larval stages of cultured spiny lobster (Jasus edwardsii) phyllosoma

Abstract: We examined biochemical changes accompanying feeding and starvation from hatch to Stage VI (day 74 after hatch) in spiny lobster, Jasus edwardsii, phyllosoma larvae. Larval dry weights (dw) increased 17-fold from hatch (80 ± 1 μg) to Stage VI (1415 ± 44 μg). Larvae starved for 6-11 days at Stages II, IV and VI were 14-40% lighter than their fed counterparts fed enriched Artemia. The increases and losses in total dw during feeding and starvation were associated with changes in the content of protein (constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 47 publications
4
41
1
Order By: Relevance
“…These results indicated that phyllosomas in CEs are in better nutritional condition than those in AEs, especially at Stage VIII when these differences had become substantial. In addition, the higher lipid : protein ratio of phyllosomas in CEs than in AEs could suggest that there is better food availability for phyllosomas in CEs than in AEs, because lipid is known to be catabolised at a greater rate than protein and carbohydrate during food deprivation of phyllosoma (Ritar et al 2003). Furthermore, experimental feeding of P. cygnus phyllosomas of the same developmental stages as examined in this current study showed that lipid is rapidly accumulated when prey are readily available (Saunders et al 2012).…”
Section: Comparison Between Ces or Aes Replicatesmentioning
confidence: 59%
“…These results indicated that phyllosomas in CEs are in better nutritional condition than those in AEs, especially at Stage VIII when these differences had become substantial. In addition, the higher lipid : protein ratio of phyllosomas in CEs than in AEs could suggest that there is better food availability for phyllosomas in CEs than in AEs, because lipid is known to be catabolised at a greater rate than protein and carbohydrate during food deprivation of phyllosoma (Ritar et al 2003). Furthermore, experimental feeding of P. cygnus phyllosomas of the same developmental stages as examined in this current study showed that lipid is rapidly accumulated when prey are readily available (Saunders et al 2012).…”
Section: Comparison Between Ces or Aes Replicatesmentioning
confidence: 59%
“…Anger et al (1985) and Harms et al (1991), studying the effect of starvation on lobsters (Homarus americanus) and of different diets on spider crabs (Hyas areneus), found significant moult cycle related changes in successive larval instars. Several nutritional studies on the early developmental stages of majoid crabs (Anger et al 1981, Dawirs 1983, Figuereido et al 2008) and other decapod crustaceans (Dawirs 1983, Harms et al 1994, Ritar et al 2003, Johnston et al 2004Narciso 2006, Sánchez-Paz et al 2007) have also used various biochemical parameters as nutritional indices, but none of these studies took into account the moult stages within individual larval or postlarval instars. The present study, as well as the studies of Anger et al (1985) and Harms et al (1991), demonstrate that there are moult cycle related changes in the biomass and biochemical parameters of larval and postlarval crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Early stages (I to III) are predominantly found in coastal waters, whereas later stages (V to XI) inhabit oceanic waters where markedly different potential prey species are present at generally far lower abundance (Bruce et al 1997). Phyllosoma development involves a phenomenal increase in body mass (several orders of magnitude; Ritar et al 2003), and the accumulation of sufficient energy stores in the final developmental stages to power the non-feeding but highly active post-larval or puerulus stage (Jeffs et al 1999).…”
Section: Introductionmentioning
confidence: 99%